Culturally based coping with COVID-19 pandemic: using constructive roles of the spiritual systems with appropriate function. (19th July 2021) - Omidvari, Sepideh
Summary: Considering the global number of confirmed COVID-19 cases and deaths, it is not strange that COVID-19 disease is a reminiscent of concepts such as death and affliction with a serious disease. Furthermore, it might remind people of issues such as the reason(s) for occurrence of deplorable events in the universe, the meaning of life, individuals' duties toward themselves and others, the relationship between the nature and human beings, and individuals' relationship with a higher being (in case there is a belief in a higher being), i.e. the subjects spirituality deals with. The constructive or destructive role of each of religious and non-religious spiritual systems at the time of crises are observed more clearly than ever. The present paper addresses roles which spiritual systems might play in facing the COVID-19 disease crisis, considering different areas of spiritual well-being and the possibility that spiritual systems might be affected by perceived challenges during a pandemic. Because of the problems interfering with overcoming COVID-19 pandemic and the risk of next waves of its epidemics and pandemics, it is necessary for health policy-makers to use all available capacities and capabilities to counteract the disease, including using both internal motivations (such as spiritual beliefs which prohibit hurting oneself and others and which emphasize performing social responsibilities) and external ones (e.g. regulations) to cope with it. It makes sense for public health officials in different countries to use more actively the potential of those spiritual systems that support COVID-19 public health recommendations, as a culturally based intervention and policy. Lay summary: COVID-19 disease might remind people of issues such as the reason(s) for occurrence of deplorable events in the universe, the meaning of life, individuals' duties toward themselves and others, the relationship between the nature and human beings, and individuals' relationship with a higher being as an omnipotent (in case there is a belief in a higher being). These are the subjects which spirituality deals with. Some spiritual packages (or say spiritual systems), religious or non-religious, might respond appropriately to our questions about the above topics and help us to get through the disasters such as COVID-19 disease with the least complications and some might not. Given what health officials and scientists have said regarding COVID-19 pandemic, it is important to adhere to those spiritual systems which could help us: - Do our best in order to prevent endangerment of our life and that of other people. - Lead, despite all the bitter facts, a meaningful life during the pandemic. - When afflicted with the disease, cope with it well and also cope with the possibility of death. - Learn the lesson 'every good thing you wish for yourself, wish it for others too, and every evil thing you do not like for yourself, do not like it for others either'.